Filosofias, religiosidades africanas e educação: reflexões sobre o processo de ensino-aprendizagem no candomblé ketu do Brasil - Santos, Ademir Barros dos (2023)
This research seeks to detect and analyze how African autochthonous philosophies influence the educational process present in the candomblé of the ketu nation active in Brazil, to identi-fy whether this is responsible for sustaining the permanence of social beacons that, developed in the continent of origin, still operate in that candomble. Methodologically, the approach to the theme is characterized as a qualitative investigation of a theoretical-bibliographical bias, using different sources, whose data were enriched with the prospection and analysis of recent speeches given by African and Brazilian historians, philosophers and sociologists, active in teaching university and available, including, in a virtual environment. For Brazilian sources, priority was given to those linked, in addition, to the culture and religiosities of African origin, either by affinity or by belonging. The analysis used socio-historical and comparative methods to historicize the genesis of the Founding Houses of that belief, as well as the permanence of the educational processes present in the studied religious environment. The Afrocentricity par-adigm served as a disciplinarian of the research, whose theme, considering the exploratory investigation carried out for the formulation of the project, was practically undetectable in Brazilian academic production until 2019, the date of the beginning of this analysis. The re-sults indicate that African autochthonous philosophies are responsible for the educational pro-cesses preserved in the candomblé studied, which are based on civilizing values that Munanga (1984, 1988) points out as universal as sub-Saharan Africa, such as vital force, community, seniority, orality, lineage and ancestry.